Predicting Teacher Burnout in Primary School Teachers: The Roles of Self-Efficacy, Emotion Regulation, Mindfulness, and School-Related Factors - Gajda, Maja; Zielińska, Anna (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
Burnout is increasingly recognized as a major occupational health concern. Teachers are particularly vulnerable due to the emotional demands of their work, high expectations, and limited institutional support. This study examined individual (self-efficacy, mindfulness, and emotion regulation) and school-related factors (satisfaction with the school environment and availability of educational resources) as predictors of two dimensions of burnout: exhaustion and disengagement. Additionally, burnout was assessed using Polish norms for the Oldenburg Burnout Inventory. Participants were 240 public elementary school teachers with over ten years of experience who completed online questionnaires. Multivariate regression analysis was used. Teachers who felt more supported and satisfied with their school environment reported lower levels of exhaustion and disengagement. Better emotion regulation and mindfulness were also associated with reduced exhaustion, while disengagement was primarily linked to emotion regulation. Self-efficacy and satisfaction with educational resources were not significant predictors. Half of the teachers scored above average on exhaustion and one-third on disengagement. These findings indicate that both personal and organizational factors play a key role in teacher well-being. Strengthening emotion regulation and mindfulness, along with fostering supportive school environments, may help reduce burnout. Limitations and implications for practice are discussed.